Pleasure, arousal, dominance, and judgments about music in everyday life - Krause, Amanda; North, Adrian (Sage Publications Ltd., 2017)
The aim of the present research was to consider what particular features are significant predictors of whether music is present in a given situation, as well as what factors influence a person’s judgments about the music. Applying Mehrabian and Russell’s (1974) Pleasure-Arousal-Dominance model to everyday experiences of music, 569 people reported on their activity for the previous day via the Day Reconstruction Method (Kahneman, Krueger, Schkade, Schwarz, & Stone, 2004). Data concerning each event included the activity and location, and characterization of the experience using the Pleasure–Arousal–Dominance measure. Moreover, for those events where music was present, participants also indicated how they heard the music and made four judgments about the music. Results indicated that the location, activity, and the person’s perception of dominance were significant predictors of the presence of music during everyday activities and that person’s judgments about the music. Contrary to prior research that has considered predominantly situational pleasure and arousal variables, the present results demonstrate that dominance is arguably the important variable in contextualized music listening.